Review of the Hydraulic and Structural Design of High-Speed Centrifugal Pumps - Hao, Yang; Hao, Jia; Zuchao, Zhu; Xianghui, Su; Wenqi, Lu; Gruszczynski, Maciej; Qiangmin, Ding; Panlong, Gao (Frontiers in Energy Research, 2022)
In recent years, much attention has been paid to the application of high-speed centrifugal pump, still the development of this pump faces several challenges. In order to obtain a more comprehensive understanding of high-speed centrifugal pump, this paper reviewed the engineering application, technical challenges and feasible solutions of this pump from the aspects of hydraulic design, including cavitation, hydraulic excitation, efficiency issue at ultra-low specific speed and the solution to these problems. The current state of structural design of high-speed centrifugal pump was briefly described in additional. For the faults in the existing high-speed centrifugal pump, some researches on pump monitoring were presented. Finally, the status and shortcomings of the design of high-speed centrifugal pump were simply analyzed and summarized. It is hoped that this paper can provide some references for the design and practical usage of high-speed centrifugal pump.